Stochastic epidemic models for emerging diseases incorporating household structure and contact tracing - Knock, Edward Stuart (2011)
In this thesis, three stochastic epidemic models for intervention for emerging diseases are considered. The models are variants of real-time, responsive intervention, based upon observing diagnosed cases and targeting intervention towards individuals they have infected or are likely to have infected, be they housemates or named contacts. These models are: